Vulnerability and Protection of Refugees in Turkey : Findings from the Rollout of the Largest Humanitarian Cash Assistance Program in the World - Cuevas, P. Facundo (World Bank and World Food Programme, 2019)
Vulnerability and Protection of Refugees in Turkey: Findings from the Rollout of the Largest Humanitarian Cash Assistance Program in the World assesses the targeting performance and benefit level design of the Emergency Social Safety Net (ESSN) program for refugees in Turkey. It also provides a comprehensive look at the vulnerability of ESSN eligible households using a multidimensional lens, drawing from novel representative data. The ESSN provides monthly cash transfers to help the most vulnerable refugees meet their basic needs, and complement Turkey’s response to the crisis. With near 4 million refugees, Turkey hosts more refugees than any other country in the world. The program is funded by the European Union member states, and implemented nationwide in partnership with the Ministry of Family, Labor and Social Services, the World Food Programme, and the Turkish Red Crescent. The study finds that the vulnerabilities of the ESSN refugee population are multiple and complex. Refugees in the ESSN program suffer from a shortage of resources today, but also resort to coping strategies that cripple their resource-generating capacity tomorrow. The ESSN targeting criteria are relatively effective in selecting the most vulnerable refugees, but exclude a share of the poor. This issue is starting to get addressed by decentralized allowances targeted with community-level information. The ESSN cash transfer value is found to be adequate to support basic needs. An untargeted design would have minimized exclusion errors, but would reach everybody with smaller transfers, insufficient to meet basic needs. Future analysis will focus on the impact of the transfers on household welfare.